Certified ethical hacker (CEH) version 9 cert guide - Gregg, Michael (Pearson, 2017)
In this best-of-breed study guide, leading expert Michael Gregg helps you master all the topics you need to know to succeed on your Certified Ethical Hacker Version 9 exam and advance your career in IT security. Michael's concise, focused approach explains every exam objective from a real-world perspective, helping you quickly identify weaknesses and retain everything you need to know.